2019
DOI: 10.1111/jipb.12739
|View full text |Cite
|
Sign up to set email alerts
|

A leaf shape mutant provides insight into PINOID Serine/Threonine Kinase function in cucumber (Cucumis sativus L.)

Abstract: Optimizing leaf shape is a major challenge in efforts to develop an ideal plant type. Cucumber leaf shapes are diverse; however, the molecular regulatory mechanisms underlying leaf shape formation are unknown. In this study, we obtained a round leaf mutant (rl) from an ethyl methanesulfonate‐induced mutagenesis population. Genetic analysis revealed that a single recessive gene, rl, is responsible for this mutation. A modified MutMap analysis combined linkage mapping identified a single nucleotide polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Wild type cucumber leaves are flat and have seven lobes with toothed or smooth margin. Three non-lobe, round leaf mutants, rl-1 , rl-2 and rl have been identified, which are all due to allelic mutations in the PINOID ( CsPID ) gene encoding a regulator for the auxin polar transporter PIN (PIN-FORMED) 11,12 .…”
Section: Genes and Qtl For Whole Plant Vegetative Growth And Developmentmentioning
confidence: 99%
“…Wild type cucumber leaves are flat and have seven lobes with toothed or smooth margin. Three non-lobe, round leaf mutants, rl-1 , rl-2 and rl have been identified, which are all due to allelic mutations in the PINOID ( CsPID ) gene encoding a regulator for the auxin polar transporter PIN (PIN-FORMED) 11,12 .…”
Section: Genes and Qtl For Whole Plant Vegetative Growth And Developmentmentioning
confidence: 99%
“…Cucumber is a typical dicotyledonous plant species that produces simple leaves; in this case, a single leaf blade is attached to the node by a petiole 34 , 36 . A typical leaf of cucumber is palmate, with five primary veins extending from the petiole at the leaf base to the leaf margins to form lobed leaf (Fig.…”
Section: Genetic Regulation Of Leaf Morphology In Cucumbermentioning
confidence: 99%
“…3B ). Fine mapping data showed that the causal gene rl encodes a homolog of the protein kinase PINOID in Arabidopsis (CsPID) 36 38 . PID is involved in the fine-tuning of polar auxin transport through phosphorylation of PIN-FORMED (PIN) proteins in Arabidopsis 39 .…”
Section: Genetic Regulation Of Leaf Morphology In Cucumbermentioning
confidence: 99%
“…In an exciting advance in the study of leaf shape, a new paper in JIPB by Song et al (2019) describes the characterization of the cucumber ( Cucumis sativus L.) round leaf ( rl ) mutant, which produces rounded leaves (Figure 1) and abnormal, female‐sterile flowers. The rl plants also have abnormal ovaries and roots with more lateral roots.…”
mentioning
confidence: 99%
“… The rl phenotype In contrast to the normal, pentagonal shapes of leaves produced by the wild‐type (WT) cucumber plant (left), the rl plant (right) produces rounded, heart‐shaped leaves (white arrows). Figure from Song et al (2019), figure 1A.…”
mentioning
confidence: 99%